A produção do espaço livre público do Parque da Prainha em Vila Velha-Espírito Santo : disputa territorial em projetos urbanos - Franchini, Filipe Barreto (2016)
The research here presented works with the goal of investigating the making of the open space of public use in Parque da Prainha, located in Vila Velha, Espírito Santo, during the period of 1989, the year the park was built, up to 2016, revealing the process of building, demolition and a possible subsequent rebuilding of the park. The methodology used in this paper envolved a bibliographic study regarding the production of space and public space, documentary research in archives and public libraries, as well as interviews with key-persons related to the history of urban occupation in Vila Velha, to the execution of the landfill and to the Prainha Park. The investigation was developed by the identification of the social agents that act upon the constant production of the open space of public use in Prainha Park, primarily the Residents’ Association; Business Association; the Fishery Groups, embarking both the Fishery Cooperative and the Fishing Colony, and the Public Power in the form of State and Municipalities. The findings in this paper reveal that the Park construction in 1990 is related to the actions of the Residents ’Association, Fishery Group and the State Public Power during the 80’s decade. After working for 19 years, the disregard towards the Park’s maintenance, the problem pointed by the Residents’ Association, like insecurity, and the interest of the Business Association to build a new Park that supports touristic practices and the tourism businesses are explanations that rise to justify the Park’s demolition in 2009. In 2016, 7 years have gone by since the demolition and the Park has not been rebuilt. For that matter, 3 urban architectural projects for rebuilding the Prainha Park were analyzed in this research. The projects show a strong economic bias towards the development and the support of touristic activities, not only the ones associated to the visitation of the historical site or the religious activities that characterizes the Prainha neighborhood, but also the strengthening of the tourism of events.